Jurist Challenges of Organ Qisas (Retaliation) in Conjoined Twins - Mahdiyeh Ghanizadeh; Ali Tavallaei; Mohammad reza Kaykha (مطالعات فقه و حقوق اسلامی, 2018)
In conjoined twins, join of body to each other results in multiplicity or unity doubt of personality. These individuals are sometime two separate and independent personalities in a common body (multiplicity twins) and some of them are a unit personality that has extra part in its body (unit twins). This is one the most important issue which gives them a distinct rule from ordinary people. The aim of current study is to investigate the criminality and victimization rules of this type of compos mentis in the case of crimes and retaliation for wounds by descriptive-analytic method. The most important findings reveal that firstly, the criteria for determining their unity or multiplicity of their character is multiplicity or unity of their vital forces such as brain and heart. Secondly if multiplicity twins commit a crime to the organ of a person that is equal to their common organ, retaliation involves paying the ransom surplus. But if the crime is committed by one of the twins, the execution of retaliation transform due to loss of the other non-criminal twin. Thirdly, if in the case of multiplicity of twins, a crime is committed by one of the common organs by one of the twins, belonging organ to both of them require the criminal twin to pay half of the compensation. Fourth, in the assumption of multiplicity; crimes committed on their common organ, cause multiplicity of victim of crime ( Majniyon- alayh) and the criminal is responsible toward both of them.